course mth 271 }KعYpKð掜_assignment #028
......!!!!!!!!...................................
20:24:16 Query 3.7.12 sketch y = -x^3+3x^2+9x-2 **** Describe your graph, including a description of any intercepts, extrema, asymptotes and concavity.
......!!!!!!!!...................................
RESPONSE --> this doesnt factor... trying numbers you get x= -2 so we have (x+2)... but then what else? i cant remember how to long divide a polynomial confidence assessment: 0
.................................................
......!!!!!!!!...................................
20:26:41 First we find the zeros: You can find the zero at x = -2 by inspection (i.e., try a few simple values of x and see if you 'hit' one). Knowing that x = -2 is a zero, you know that (x - (-2) ) = x + 2 is a factor of the expression. You can find the other factor by long division of x + 2 into -x^3 + 3 x^2 + 9x - 2. You get quotient x^2 - 5 x + 1. Thus -x^3 + 2 x^2 + 9 x - 2 = - (x + 2)(x^2 - 5x + 1). This expression is zero when x+2 = 0 or when x^2 - 5 x + 1 = 0. The first equation we already know gives us x = -2. The second is solved by the quadratic formula. We get x = [ -(-5) +- `sqrt( (-5)^2 - 4 * 1 * 1 ) ] / (2 * 1) = [ 5 +- `sqrt(21) ] / 2. Simplifying we get approximate x values .21 and 4.7. Then we find maxima and minima using 1st and 2d derivative: The derivative is -3x^2+6x + 9, which gives the equation -3x^2+6x + 9 = 0 for critical points. Dividing thru by -3 we get x^2 - 2x - 3 = 0 or(x-3)(x+1) = 0 so x = 3 or x = -1. Second derivative is -6x + 6, which is negative when x = 3 and positive when x = -1. At x = 3 we have a maximum. Evaluating y = -x^3+3x^2+9x-2 at x = 3 we get y = 25. The negative second derivative indicates that (3,25) is a maximum. At x = -1 we have a minimum. Evaluating y = -x^3+3x^2+9x-2 at x = -1 we get y = -7. The positive second derivative indicates that this (-1,-7) is a minimum. Finally we analyze 2d derivative for concavity and pts of inflection: The second derivative -6x + 6 is zero when x = 1; at this point the derivative, which is linear in x, changes from positive to negative. Thus the x = 1 point (1, 9) is a point of inflection. The derivative is positive and the function therefore concave up on (-infinity, 1). The derivative is negative and the function therefore concave down on (1, infinity). The function is defined for all x so there are no vertical asymptotes. As | x | -> infinity the magnitude of the function -> infinity so there are no horizontal asymptotes. **
......!!!!!!!!...................................
RESPONSE --> okay so you use 1st deriv to find max and min and the 2nd deriv to find concavity and pts of inflection? and you only test concavity on the intervals using the points of inflection? self critique assessment: 1
.................................................
......!!!!!!!!...................................
20:30:51 Query 3.7.34 sketch (x^2+1)/(x^2-1) Note: The problem in the text might be (x^2+1)/(x^2-2). If so the solution given below can be easily adapted to that function. Describe your graph, including a description of any intercepts, extrema, asymptotes and concavity.
......!!!!!!!!...................................
RESPONSE --> looking at the numerator, there are no zeros f'(x)=-4x/(x^2-1)^2) -4x=0, x=0 is crit pt f''(x)=(4(3x^2+1))/(x^2-1)^3) vert asymp at x= 1, -1 2nd deriv test: (-i,-1) (-1,1) (1,i) + - + up down up confidence assessment: 2
.................................................
......!!!!!!!!...................................
20:32:17 First we look for zeros and intercepts: The numerator is never zero, being the sum of the positive number 1 and the nonnegative quantity x^2. So the function has no zeros, i.e., never crosses the x axis. When x=0 we have y = (0^2+1)/(0^2-1) = -1 so the y intercept is (0,-1). Next we analyze the derivative to see if we can find relative maxima and minima: The derivative is - 4x/(x^2 - 1)^2, which has its only zero when x = 0. So (0, -1) is the only critical point. The second derivative is 4(3x^2 + 1)/(x^2 - 1)^3, which is negative when x = 0. So the critical point gives us a maximum. We analyze the second derivative to determine concavity: The second derivative 4(3x^2 + 1)/(x^2 - 1)^3 has a numerator which is always positive, since x^2 is always positive. The denominator is negative where x^2 - 1 < 0, which occurs between x = -1 and x = 1. So the 2d derivative is positive on (-infinity, -1) and on (1, infinity), where the graph will be concave up, and negative on (-1, 1), where the graph will be concave down. Now we look for vertical and horizontal asymptotes: The denominator of (x^2+1)/(x^2-1) is zero and the numerator isn't when x = +1 and also when x = -1. So we have vertical asymptotes at x = +1 and at x = -1. }For very large positive x or for very large negative x the +1 in the numerator and the -1 in the denominator are both insignificant and the function value is very close to x^2 / x^2 = 1. The function approaches its horizontal asymptote y = 1 for both large positive x and large negative x. We finally determine where the function is positive and where negative: For x < -1 the function cannot change sign, since it is continuous and has no zeros. Testing any x < -1 gives us a positive value. On this interval the function is therefore positive. The same is true for x > 1. For -1 < x < 1 the same argument shows that the function is negative**
......!!!!!!!!...................................
RESPONSE --> seems like excess verbiage... am i missing something in my answer? self critique assessment: 2
.................................................
օF} assignment #029 029. `query 29 Applied Calculus I 12-10-2007
......!!!!!!!!...................................
20:42:35 Query 3.8.6 differential of cube root of (6x^2) **** Give the differential of the expression and explain how you obtained it.
......!!!!!!!!...................................
RESPONSE --> chain rule y'=4x(6x^2)^(-2/3) y'=4x/((6x^2)^(2/3)) dy=((4x)/((6x^2)^(2/3))dx confidence assessment: 3
.................................................
......!!!!!!!!...................................
20:42:48 dy is the differential; `dy means 'delta-y' and is the exact change. y = (6x^2)^(1/3) y' = dy/dx = 1/3(6x^2)^(-2/3)(12x) y' = dy/dx = 4x(6x^2)^(-2/3) y' = dy/dx = 4x / (6x^2)^(2/3). So dy = (4x / (6x^2)^(2/3)) dx **
......!!!!!!!!...................................
RESPONSE --> yup self critique assessment: 3
.................................................
......!!!!!!!!...................................
20:50:34 ** Query 3.8.12 compare dy and `dy for y = 1 - 2x^2, x=0, `dx = -.1 **** What is the differential estimate dy for the given function and interval, and what is the actual change `dy?
......!!!!!!!!...................................
RESPONSE --> y'=-4x dy=-4x(dx) dy=-4(0)(-.1) dy=0 actual change is f(x+dx)-f(x) f(0-.1)-f(0) f(-.1)-f(0)= (1-2(-.1)^2)-(1-0)= -.02 self critique assessment: 3
.................................................
......!!!!!!!!...................................
20:50:43 y ' = dy /dx = - 4 x so dy = -4x dx. The differential estimate is dy = -4 * 0 * (-.1) = 0. Actual change is y(x + `dx) - y(x) = y(0 - .1) - y(0) = (1 - 2 ( -.1)^2) - (1-0) = -.02. **
......!!!!!!!!...................................
RESPONSE --> yup self critique assessment: 3
.................................................
......!!!!!!!!...................................
20:57:52 Query Extra Problem: Give the equation of the tangent line to y= 2 * x^(1/3) - 1 at (8,3); tan line prediction and actual fn value at `dx = -.01 and .01. **** What is the equation of the tangent line and how did you obtain it?
......!!!!!!!!...................................
RESPONSE --> f'(x)=2/3x^(-2/3) f'(8)=2/3(8)^(-2/3) f'(8)=1/6 pt slope: y-3=1/6(x-8) y=1/6x+5/3 dx=.01, then x+dx=8.01 y=1/6(8.01)+5/3= 3.001666666 tan approx actual 2(8.01)^(1/3)-1= 3.001665972 dx=-.01, then x+dx= 7.99 y=1/6(7.99)+5/3= 2.998333333 tan approx actual 2(7.99)^(1/3)-1= 2.998332638 confidence assessment: 3
.................................................
......!!!!!!!!...................................
20:58:09 f(x) = 2x^(1/3) - 1 f' (x) = 2/3x ^(-2/3) f ' (8) = 2/3(8)^(-2/3) f ' (8) = 1/6 y - 3 = 1/6(x - 8) y - 3 = 1/6x - 8/6 y = 1/6x + 10/6 y = (1/6)x + (5/3) after simplification. Using `dx = .01 we get x + `dx = 8.01. The tangent-line approximation is thus y = 1/6 * 8.01 + 5/3 = 3.001666666. The actual function value is 2 * 8.01^(1/3) - 1 = 3.001665972. The difference is .0000007, approx. A similar difference is found approximating the function for `dx = -.01, i.e., at 7.99. We see that for this short interval `dx the tangent-line approximation is very good, predicting the change in the y value (approximately .001666) accurate to 4 significant figures. COMMON ERROR: Students often round off to 3.0017, or even 3.002, which doesn't show any discrepancy between the tangent-line approximation and the accurate value. Taken to enough decimal places the values of the function and the tangent-line approximation do not coincide; this must be the case because the function isn't linear, whereas the tangent line approximation is. You should in general use enough significant figures to show the difference between two approximations. The difference should be no greater than -.02 * .01^2 = -.000002 (based on a Taylor's Theorem estimate I did in my head so don't hold me responsible for its accuracy, and you aren't responsible for Taylor's Theorem at this point of the course); the discrepancy might therefore appear in the 6th decimal place, almost certainly not later than the 7th. **
......!!!!!!!!...................................
RESPONSE --> yup self critique assessment: 3
.................................................
......!!!!!!!!...................................
21:02:16 **** Query 3.8.42 drug concentration C = 3t / (27+t^3) **** When t changes from t = 1 to t = 1.5 what is the approximate change in C, as calculated by a differential approximation? Explain your work.
......!!!!!!!!...................................
RESPONSE --> c'=(81-6t^3)/((27+t^3)^2) dc= ((81-6t^3)/((27+t^3)^2))dx t=1 dt=.5 dc= ((81-6(1)^3)/((27+(1)^3)^2)).5 dc=.0478 mg/ml confidence assessment: 3
.................................................
......!!!!!!!!...................................
21:02:31 By the Quotient Rule we have C' = ((3) (27 + t^3) - (3t^2)(3t))/ (27 + t^3)^2, or C' = (81 - 6t^3) / (27 + t^3)^2. The differential is therefore dC =( (81 - 6t^3) / (27 + t^3)^2) dx. Evaluating for t = 1 and `dt = .5 we get dC = ((81 - 6(1)^3) / (27 + (1)^3)^2) * (.5) dC = (75 / 784) (.5) dC = .0478 mg/ml **
......!!!!!!!!...................................
RESPONSE --> yup self critique assessment: 3
.................................................